Long-term exposure to multiple air pollutants and multi-level socioeconomic status: joint effects on age-related macular degeneration, subsequent ocular comorbidity, and death in middle-aged and older adults - Yang Yang; Liangkai Chen; Qichen Liu; Min Mu; Jing Huang; Guangming Zhang; Qianqian Song (BMC Medicine)
Abstract Background Both air pollution and socioeconomic status (SES) are recognized as significant determinants of health outcomes. However, no study has explored the combined effects of air pollutants and SES on (1) age-related macular degeneration (AMD) incidence; (2) trajectories from baseline to AMD, subsequent ocular comorbidity (OCMD), and mortality; and (3) life expectancy in middle-aged and older adults. Methods Using UK Biobank data, we created two composite air pollution scores (APS) and assessed SES at individual and neighborhood levels. OCMD was defined as glaucoma or cataract occurrence after AMD diagnosis. Cox proportional hazard regression models, multistate models, and life tables were used to assess associations and calculate life expectancy. Results Over a median of 12.5 years, 3859 participants developed AMD, 2907 participants developed OCMD, and 23,363 died. Compared to those with low APS and favorable SES, individuals with high APS and unfavorable SES had highest risk (APS1: individual-level SES HR 1.41, 95% CI: 1.18–1.67, area-level SES HR 1.31, 95% CI: 1.15–1.49; APS2: individual-level SES HR 1.51, 95% CI: 1.27–1.80; area-level SES HR 1.31, 95% CI: 1.15–1.49), after adjusting for all potential covariates. Among five transitions, the combined effects were significant in transitions from baseline to incident AMD, from AMD to OCMD, and from baseline to death. Significant life expectancy disparities were observed; individuals with low individual-level SES had shortest life expectancies across APS tertiles, with similar but less pronounced effects for area-level SES. Conclusions Our study underscores the need for interventions addressing air pollution and SES to reduce AMD risk, improve ocular health, and enhance life expectancy in aging populations.